Ograniczenia w podejmowaniu dodatkowych zajęć i zatrudnienia przez notariuszy - Tkaczyński, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Article 19 of the Polish Public Notary Law imposes limitations on public notary workers with regard to undertaking commissioned work outside their main public notary work. This provision, however, is unclear in its interpretation. The article considers the scope of the norm included in the above-mentioned provision and indicates that the norm undoubtedly relates to public notary workers, public notary trainees, associate public notaries and retired public notaries, but it does not include candidates to a public notary position. Further in the article, the author makes a clear division of notions referring to work and activities that bring profit but not necessarily bring a profit outside the main public notary work. The above division shows different procedures of obtaining permission from the Council of the Chamber of Public Notaries RIN. In case of employment outside of the main notary work, advance consent has to be granted. Such consent is not required for work as an academic teacher. RIN, however, can occasionally terminate the employment if it interferes with public notary work. The division results in RIN’s preventative control over the impact an employment will have on the main work of public notary. Commissioned work can be more complex due to a broader interpretation of this notion. This means that a public notary has the duty to report any commissioned work, but they do not have to postpone its commencement until the consent is granted. If the consent is not granted, the notary must terminate any commissioned work with immediate effect. The article considers various types of employment, starting from self-employment to legal person functions, to capital investments. The article also presents the law as it ought to be regarding a simplification and clarification of Article 19 of the Public Notary Law.
Keywords: notariusz; zatrudnienie; praca; pozwolenie; obowiązek